Influence of Perinatal Factors on Blood Tryptase and Fecal Calprotectin Levels in Newborns - Justine Paysal; Charlotte Oris; Ugo Troin; Pierre-Nicolas Limeri; Jeanne Allard; Marie Tadrent; Bruno Pereira; Etienne Merlin; Emmanuelle Rochette; Bertrand Evrard; Julie Durif; Vincent Sapin; et al. (Children, 2023)
Background: Blood tryptase and fecal calprotectin levels may serve as biomarkers of necrotizing enterocolitis. However, their interpretation may be hindered by the little-known effects of perinatal factors. The aim of this study was to compare the tryptase and calprotectin levels in newborns according to their term, trophicity, and sex. Method: One hundred and fifty-seven premature newborns and 157 full-term newborns were included. Blood tryptase and fecal calprotectin were assayed. Results: Blood tryptase levels were higher in premature than in full-term newborns (6.4 vs. 5.2 µg/L; p < 0.001). In situations of antenatal use of corticosteroids (p = 0.007) and non-exclusive use of human milk (p = 0.02), these levels were also higher. However, in multiple linear regression analyses, only prematurity significantly influenced tryptase levels. Fecal calprotectin levels were extremely wide-ranging and were much higher in female than in male newborns (300.5 vs. 110.5 µg/g; p < 0.001). Conclusions: The differences in tryptase levels according to term could be linked to early aggression of the still-immature digestive wall in premature newborns, in particular, by enteral feeding started early. The unexpected influence of sex on fecal calprotectin levels remains unexplained.